Periodontal Infection Aggravates C1q-Mediated Microglial Activation and Synapse Pruning in Alzheimer’s Mice - Hao, Xiaoxiao; Li, Zhaofei; Li, Wei; Katz, Jannet; Michalek, Suzanne M.; Barnum, Scott R.; Pozzo-Miller, Lucas; Saito, Takashi; Saido, Takaomi C.; Wang, Qin; Roberson, Erik D.; Zhang, Ping (Frontiers in Immunology, 2022)
Periodontitis is a dysbiotic infectious disease that leads to the destruction of tooth supporting tissues. There is increasing evidence that periodontitis may affect the development and severity of Alzheimer’s disease (AD). However, the mechanism(s) by which periodontal infection impacts the neurodegenerative process in AD remains unclear. In the present study, using an amyloid precursor protein (APP) knock-in (App KI) AD mouse model, we showed that oral infection with Porphyromonas gingivalis (Pg), a keystone pathogen of periodontitis, worsened behavioral and cognitive impairment and accelerated amyloid beta (Aβ) accumulation in AD mice, thus unquestionably and significantly aggravating AD. We also provide new evidence that the neuroinflammatory status established by AD, is greatly complicated by periodontal infection and the consequential entry of Pg into the brain via Aβ-primed microglial activation, and that Pg-induced brain overactivation of complement C1q is critical for periodontitis-associated acceleration of AD progression by amplifying microglial activation, neuroinflammation, and tagging synapses for microglial engulfment. Our study renders support for the importance of periodontal infection in the innate immune regulation of AD and the possibility of targeting microbial etiology and periodontal treatment to ameliorate the clinical manifestation of AD and lower AD prevalence.